Implementing Educational Technology in the Classroom to Teach English Skills: A Systematic Literature Review - Amanda Pradhani Yanwar; Jirarat Sitthiworachart; Mike Joy (Journal of Higher Education Theory and Practice, 2022)
Technology is getting more sophisticated in today’s globalized world. Technology also provides educational technology tools, including in English teaching and learning. It aims to support and assist teachers and students to obtain a better English teaching and learning experience. This paper focuses on the implementation of educational technologies in English classrooms. The analysis of the included studies shows that: (1) true experiments, quasi-experiments, and causal-comparative research were the research methods used in the studies; (2) 8 types of educational technologies were found to be implemented in the studies; (3) a variety of relationship between educational technology tools and English skills were identified. This paper also shows that there had been little research regarding English skills (listening, reading, grammar, and pronunciation) in the context of educational technology. Finally, this study provides other significant information on limitations and implications followed by a conclusion.
Keywords: Technology-Enhanced Education Studies